Protein purification by using immobilized metal ions affinity zeolite adsorbent - Su Najwa, Mohamed (2010)
The applications for purified proteins have grown considerably over recent years due to their biological and nutritional properties. The aim of this research are to develop zeolite as inorganic stationary substrate in immobilized metal ion affinity (IMA) for protein purification and to study the optimum condition to purify protein in order to maximize yield and purity of protein by applying the principle of adsorption process. The effect of contact time, different types of adsorbent and various pH values were studied in a batch experiment by using Bovine Serum Albumin (BSA) as protein sample. The sorption equilibrium was reached within 10 minutes. Fe3+ ion showed the best performance for BSA and has the suitable interaction with both HY and HBeta zeolite framework and the protein as compared to Pb2+, Ni2+ ions. The adsorption capacity for BSA was found to be the highest at pH 4.5 that is close to isoelectric point (pI) with Fe- HBeta used as adsorbent. The adsorbed amount increases as the pH increases and reduces as the pH exceeds the pI value. This result proves that adsorption capacity of Bovine Serum Albumin depends on the types of adsorbent used, which means the adsorption stoichiometries depends on physical characteristic of adsorbent that could increase and reduce the adsorption capacity of the protein as well as the pH of protein. The adsorption isotherm data of BSA is well fitted to the Langmuir isotherm model.